"Improving The Teaching Of" Education "On the Basis of Multimedia Technologies" (On the Example of Primary Classes) - Sidikova Zulfiyaxon Murodjon qizi.; Aminov Aminjon Inomzoda (Zien Journals, 2021)
The article analyzes the initial pedagogical processes in the direction of primary education students to the profession, and in this process the teacher's pedagogical skills, knowledge and skills related to the choice of profession, as well as personality traits in the choice of profession, the psychology of the reader, the criteria indicating the readiness of students to choose a profession, the content Methodological recommendations on the topic have been developed.
Keywords: Teacher; pupil; primary education; profession